Buffered delivery of phosphate to Arabidopsis alters responses to low phosphate - Hanlon, Meredith T; Ray, Swayamjit; Saengwilai, Patompong; Luthe, Dawn; Lynch, Jonathan P; Brown, Kathleen M (Journal of experimental botany, 2018)
The responses of Arabidopsis to low-phosphate conditions are different from previously described when phosphate is supplied through solid-phase buffered delivery that approximates soil chemistry. Abstract Arabidopsis has been reported to respond to phosphate (Pi) stress by arresting primary root growth and increasing lateral root branching. We developed a system to buffer Pi availability to Arabidopsis in gel media systems by charging activated aluminum oxide particles with low and sufficient concentrations of Pi, based on previous work in horticultural and sand culture systems. This system more closely mimics soil chemistry and results in different growth and transcriptional responses to Pi stress compared with plants grown in standard gel media. Low Pi availability in buffered medium results in reduced root branching and preferential investment of resources in axial root growth. Root hair length and density, known responses to Pi stress, increase in low-buffered Pi medium. Plants grown under buffered Pi conditions have different gene expression profiles of canonical Pi stress response genes as compared with their unbuffered counterparts. The system also eliminates known complications with iron (Fe) nutrition. The growth responses of Arabidopsis supplied with buffered Pi indicate that the widely accepted low-Pi phenotype is an artifact of the standard gel-based growth system. Buffering Pi availability through the method presented here will improve the utility and accuracy of gel studies by more closely approximating soil conditions.